The Effect of Training and Competence on Employee Productivity at Cv Telaga Mas Bengkulu - Reskyana, Wita Fitria; Nasution, Suswati; Zoniarti, Zoniarti (Universitas Dehasen Bengkulu, 2024)
SDM always plays an active and dominant role in every organizational activity, because humans are the planners, actors and determinants of the realization of organizational goals. Work Environment and Motivation are important because with a Work Environment and Motivation every employee will want to work hard and enthusiastically to achieve higher performance. The aim of the research is to find out whether there is an influence of work environment and motivation on employee performance at the Regional Secretariat of South Bengkulu Regency. This type of research is using quantitative research. The quantitative approach is a research method based on the philosophy of potivism, used to examine certain populations or samples. The population in this study were all ASN employees at the Regional Secretariat of South Bengkulu Regency, totaling 112 ASN employees. The results of the multiple linear regression analysis Y = 2.271 + 0.257 X1 + 0.574 X2 this illustrates that the value of the Work Environment (X1) and the value of Motivation (X2) affect employee performance (Y) by 91.5% while the remaining 8.5% are influenced by other variables not examined in this study. From the results of calculations using SPSS, it can be seen that the coefficient of determination of R square is 0.915. This means that the value of the Work Environment (X1) and the value of Motivation (X2) has an effect on employee performance (Y) of 91.5% while the remaining 8.5% is influenced by other variables not examined in this study.